STRATEGI PEMERINTAH MENGATASI KELANGKAAN PUPUK ANORGANIK MELALUI COLLECTIV ACTION DI DESA MATTIROWALIE - Ramadhan, Aidil Dwi; Rusli, A. M.; Irwan, A. Lukman (JURNAL DARMA AGUNG, 2024)
Collective Action according to Muhammad Abdan Shadiqi 2021, which is a social movement that emerges from community groups with the aim of improving the condition of their groups, problems that arise in the community such as overcoming the scarcity of inorganic fertilizers that occur in Mattirowalie Village, Maniangpajo District, Wajo Regency are problems that arise due to the Government's lack of attention to the community, especially farmers in Mattirowalie Village, So that the community takes collective action with the aim of improving the condition of their group. The results of the research in this study show that the community's collective action in overcoming the scarcity of fertilizer in Mattirowalie Village has gone well, marked by actions carried out in groups, namely farmer group deliberations and carried out individually, namely the use of organic fertilizers and the implementation of farmer cards has gone well in collaboration with the Village Government and the community.